Pengaruh Perputaran Aktiva Tetap Terhadap Return On Assets Pada PT. BPRS HIK Parahyangan Bandung - Kunto Ajibroto; Nur Azizah; Hendriady De Keizer (JPS (Jurnal Perbankan Syariah), 2021)
The level of efficiency of a company in utilizing fixed assets can be measured by calculating the turnover of fixed assets to measure the level of profit generated in relation to its fixed assets by calculating the profitability ratio, proxied by return on assets. This study aims to determine the effect of fixed asset turnover on return on assets at PT. BPRS HIK Parahyangan Bandung. The research method used is descriptive with quantitative data types. While the type of research is explanatory level research that explains the position of the variables studied and the relationship between one variable and another. Data collection techniques using documentation, interviews and literature study. The data analysis technique used simple linear regression analysis. The results obtained show that there is no influence between the turnover of fixed assets on the return on assets at PT. BPRS HIK Parahyangan Bandung.